Notes on Early Land Plants Today. 57. Cheilolejeunea boliviensis and Cheilolejeunea savesiana, two new synonyms in Lejeunea (Marchantiophyta, Lejeuneaceae) - Qiu, Qiong; Wei, Y.-M.; Cheng, Xia-Fang; Zhu, Rui-Liang (Phytotaxa, 2014)
Cheilolejeunea boliviensis Stephani (1916: 266) is a poorly known species from Bolivia. It was listed as a doubtful taxon by Gradstein et al. (2003). Cheilolejeunea savesiana Stephani (1895: 244) is also a doubtful species and was treated as Lejeunea sp. in Reiner-Drehwald & Grolle (2012)’s review of Rectolejeunea Evans (1906: 8).